On expansive chaotic maps in G-spaces - Abid, Salah; Kadhim, Ihsan (International Journal of Applied Mathematical Research, 2014)
In this paper we define expansive maps in general topological space (not necessarily metrizable space) and generalize this definition to G-spaces and give some propertie of such maps. Also we study some properties of new type of chaotic maps which we called G-expansive chaotic maps. Keywords: G- Periodic Points, G-Orbits, G-Expansive Maps, G-Expansive Chaos.